Assessing students' disciplinary and interdisciplinary understanding of global carbon cycling. Issue 3 (24th October 2017) - You, Hye Sun; Marshall, Jill A.; Delgado, Cesar
Abstract: Global carbon cycling describes the movement of carbon through atmosphere, biosphere, geosphere, and hydrosphere; it lies at the heart of climate change and sustainability. To understand the global carbon cycle, students will require interdisciplinary knowledge . While standards documents in science education have long promoted interdisciplinary understanding, our current science education system is still oriented toward single‐discipline‐based learning. Furthermore, there is limited work on interdisciplinary assessment. This article presents the validated Interdisciplinary Science Assessment of Carbon Cycling (ISACC), and reports empirical results of a study of high school and undergraduate students, including an analysis of the relationship between interdisciplinary items and disciplinary items. Many‐faceted Rasch analysis produced detailed information about the relative difficulty of items and estimates of ability levels of students. One‐way ANCOVA was used to analyze differences among three grade levels: high school, college Freshman–Sophomore, college Junior–Senior, with number of science courses as a covariate. Findings indicated significantly higher levels of interdisciplinary understanding among the Freshman–Sophomore group compared to high school students. There was no statistically significant difference between Freshman–Sophomore group and Junior–Senior group. Items assessing interdisciplinary understanding were more difficult than items assessing disciplinary understanding of global carbon cycling; however, interdisciplinary and disciplinary understanding were strongly correlated. This study highlights the importance of interdisciplinary understanding in learning carbon cycling and discusses its potential impacts on science curriculum and teaching practices.